What does a healthcare professional look like? - Raj, Vayan (Research and Humanities in Medical Education, 2021)
When you meet a person with a disability, do you see the person’s disability before you see the person? What if they are healthcare professionals with disabilities? This illustration challenges our unconscious biases about the abilities of health professionals with disabilities and the lack of diversity and inclusion within the health professions. This is my original illustration depicting healthcare professionals who are part of this community.